Enhancing malaria detection in resource-limited areas: A high-performance colorimetric LAMP assay for Plasmodium falciparum screening. - Tuyet Kha Nguyen; Hojong Jun; Johnsy Mary Louis; Ernest Mazigo; Wang-Jong Lee; Hyun Cher Youm; Jieun Shin; Douglas K Lungu; Creto Kanyemba; Md Atique Ahmed; Fauzi Muh; Se Jin Lee; et al. (PLoS ONE, 2024)
Malaria eradication efforts in resource-limited areas require a rapid, economical, and accurate tool for detecting of the low parasitemia. The malaria rapid diagnostic test (mRDT) is the most suitable for on-site detection of the deadliest form of malaria, Plasmodium falciparum. However, the deletions of histidine rich protein 2 and 3 genes are known to compromise the effectiveness of mRDT. One of the approaches that have been explored intensively for on-site diagnostics is the loop-mediated isothermal amplification (LAMP). LAMP is a one-step amplification that allows the detection of Plasmodium species in less than an hour. Thus, this study aims to present a new primer set to enhance the performance of a colorimetric LAMP (cLAMP) for field application. The primer binding regions were selected within the A-type of P. falciparum 18S rRNA genes, which presents a dual gene locus in the genome. The test result of the newly designed primer indicates that the optimal reaction condition for cLAMP was 30 minutes incubation at 65°C, a shorter incubation time compared to previous LAMP detection methods that typically takes 45 to 60 minutes. The limit of detection (LoD) for the cLAMP using our designed primers and laboratory-grown P. falciparum (3D7) was estimated to be 0.21 parasites/μL which was 1,000-fold higher than referencing primers. Under optimal reaction condition, the new primer sets showed the sensitivity (100%, 95% CI: 80.49-100%) and specificity (100%, 95% CI: 94.64-100%) with 100% (95% CI: 95.70-100%) accuracy on the detection of dried blood spots from Malawi (n = 84). Briefly, the newly designed primer set for P. falciparum detection exhibited high sensitivity and specificity compared to referenced primers. One great advantage of this tool is its ability to be detected by the naked eye, enhancing field approaches. Thus, this tool has the potential to be effective for accurate early parasite detection in resource-limited endemic areas.